Prevalence of antimicrobial resistant genes in Bacteroides spp. isolated in Oita Prefecture, Japan. Issue 3 (March 2023) - Hashimoto, Takehiro; Hashinaga, Kazuhiko; Komiya, Kosaku; Hiramatsu, Kazufumi
Abstract: Introduction: Bacteroides spp. are the most common anaerobic bacteria isolated from the human gastrointestinal tract. Several resistant genes are present in Bacteroides spp. However, most studies have focused on the prevalence of the c ﬁ A gene in Bacteroides fragilis alone. We assessed the susceptibility to antimicrobial agents and the prevalence of cepA, cfiA, cfxA, ermF, nim, and tetQ genes in Bacteroides strains isolated from clinical specimens in our hospital. Methods: We isolated 86 B. fragilis and 58 non- fragilis Bacteroides strains from human clinical specimens collected from January 2011 to November 2021. Resistance against piperacillin (PIPC), cefotaxime (CTX), cefepime (CFPM), meropenem (MEPM), clindamycin, and minocycline was determined. Results: The resistant rates of penicillins and cephalosporins in non- fragilis isolates were significantly higher than those in B. fragilis isolates. In B. fragilis isolates, the resistant rates of PIPC, CTX, and CFPM in cfxA- positive isolates were significantly higher than those in cfxA- negative isolates (71% vs. 16%, 77% vs. 19%, and 77% vs. 30%, respectively). Thirteen B. fragilis isolates harbored the cfiA gene, two of which were resistant to MEPM. Six of the 13 cfiA -positive B. fragilis isolates were heterogeneously resistant to MEPM. Conclusion: It is important to evaluate the use of MEPM as empirical therapy for Bacteroides spp. infections, considering the emergence of carbapenem resistance during treatment, existence of MEPM-resistant strains, and heterogeneous resistance.